Golden code based transmission schemes and decoding methods for MIMO downlink system with finite-bit feedback - Sisi ZHENG; Haiquan WANG; Guobin LI; Tanming DAI (Dianxin kexue)
For a MIMO downlink system with finite-bit feedback,combined with the Golden code and the precoding technology,a new precoding design criterion and its related codeword selection method,transmissionschemes and corresponding low complexity decoding methods were proposed.In fact,based on fully utilizing the characteristics that the Golden code could overcome the channel depth fading,a double precoding matrix was constructed as transmission signals by using the selected precoding codeword,so that the decoding complexity could be reduced to linear.In the meantime,a joint ML and MMSE decoding method was proposed for the traditional transmission scheme,which could dynamically adjust the decoding complexity based on a threshold.The numerical simulation results confirm the superiority of the proposed schemes and methods.